Analisis Profitabilitas Usaha Pada Toko Rais Kecamatan Tenggarong - Abdullah, Rahim (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2008)
From anlysis result which is done so has been got Gross Pofit Margin in 2007 as many 22 % this value explain that every sale rupiah resulted gross profit as many Rp. 0,22 or operation cost which is comed out can be covered as many 78 % (100 % - 22 %). If compare with 2008, Gross Profit Margin as many 22, 97 % this value explain that every sale rupiah resulted gross profit Rp. 0,23 or operation cost which is comed out can be covered as many 77,03 %.The result of Net Profit Margin in 2007 which is resulted from Toko Rais as many 18,01 % that means net profit from every sale rupiah which is done as many Rp. 0,18 % (18,01 % x Rp. 1,-) or can recover sale basic cost and operation cost as many 81,99 % (100 % - 18,01 %). If compare with 2008, so Net Profit Margin increase 1,47 % because Net Profit Margin as many 19,48 %. Key Word : Profitability